Gene Effects and Heritability for Yield Traits in Tomato (Solanum Lycopersicum L.) (Bangladesh Journal of Botany, 2021)
Generation mean analysis is a key determinant in designing the appropriate breeding approaches for implementing new desirable character/s in crop varieties and also in studying inheritance of quantitative traits. Parents, F1, F2 and backcrosses exhibited significant digenic interactions in the majority of cross combinations in tomato. Cross combinations and characters indicated the adequacy of simple additive dominance for 50% flowering (CO3 х Floradade, Pant T3 х Azad T5), branches/plant and plant height (CO3 х Floradade, Pant T3 х Kashi Sharad), and fruit/cluster (CO3 х Floradade) indicating absence of non-allelic interactions. Duplicate type of epistasis occurred for 50% flowering (CO3 х Floradade, Kashi Amrit х Kashi Sharad), branches/plant (CO3 х Floradade, Kashi Amrit х Kashi Sharad, Pant T3 х Kashi Sharad), plant height (CO3 х Floradade, Pant T3 х Kashi Sharad), fruit/plant (CO3 х Floradade, Pant T3 х Azad T5, Kashi Amrit х Kashi Sharad, Pant T3 х Kashi Sharad), fruit weight (CO3 х Floradade, Pant T3 х Azad T5), fruit/cluster (Kashi Amrit х Kashi Sharad, Pant T3 х Kashi Sharad), yield/plant (CO3 х Floradade, Punjab Upma х Azad T5, Pant T3 х Kashi Sharad) indicating selection strength should be lenient in the earlier and rapid in later generations because advancement should be through selection. Characters governed by additive components were predominant in fruit/plant and plant height, indicating direct selection for improvement of these traits.Bangladesh J. Bot. 50(3): 453-465, 2021 (September)